2018
DOI: 10.1007/s11103-018-0756-3
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobia promote the growth of rice shoots by targeting cell signaling, division and expansion

Abstract: The growth-promotion of rice seedling following inoculation with Sinorhizobium meliloti 1021 was a cumulative outcome of elevated expression of genes that function in accelerating cell division and enhancing cell expansion. Various endophytic rhizobacteria promote the growth of cereal crops. To achieve a better understanding of the cellular and molecular bases of beneficial cereal-rhizobia interactions, we performed computer-assisted microscopy and transcriptomic analyses of rice seedling shoots (Oryza sativa)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…7). Such induction of D-like cyclins (here: CYCD1, D2 and D3) was also reported in rice seedlings when treated with S. meliloti (Wu et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
“…7). Such induction of D-like cyclins (here: CYCD1, D2 and D3) was also reported in rice seedlings when treated with S. meliloti (Wu et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, previous studies revealed that the inoculation of beneficial rhizobacteria induced the regulation of at least 1,000 genes in rice roots at earlier time points after inoculation (Drogue et al, 2014; Brusamarello-Santos et al, 2019; Rekha et al, 2018). Moreover, compared with the only study that analyzed the leaf transcriptional response of rice to the inoculation by beneficial rhizobacteria that retrieved only 2,414 DEGs at early stages of the interaction (Wu et al, 2018), when our study identified data of at least 4,000 DEGs in leaves in response to both strains.…”
Section: Discussionmentioning
confidence: 89%
“…It is well known that inoculation of rhizobia also helps to save the N source for cereal production, thus, reducing the application of N fertilizers which in turn conserves the environment [31,[37][38][39][40]. Interestingly, Wu et al indicated that inoculation of rice with one species of rhizobia, Sinorhizobium meliloti, helped rice growth by elevating the expression of genes that function to enhance cell expansion and accelerate cell division [41]. Furthermore, another study revealed that the alliance of arbuscular mycorrhizal (Glomus mosseae) and rhizobial (R. leguminosarum) symbioses alleviated damage to clover (Trifolium repens) by root hemiparasitic Pedicularis species [42].…”
Section: Plant Growth-promoting Bacteriamentioning
confidence: 99%